Investigation of safety conditions in the transport of dangerous goods by railway - Slavinskaitė, Neringa; Batarlienė, Nijolė (Transport, 2022)
Safe transport of dangerous goods by railway is an important challenge for both national and international freight transport. The transport of dangerous goods is one of the most demanding transportation technologies. The aim of this article is to assess the conditions for the transport of dangerous goods by railway and to define the main factors, which affect the transport of such goods by railway. Scientific literature was analysed, statistics were provided, and a qualitative survey was conducted. The factors of 3 groupas that have the greatest impact on the safe transport of dangerous goods by railway were studied and identified. The obtained results were processed using the Kendall’s rank correlation method, and the consistency of the expert opinions was clarified using the fit coefficient. Using the medium-distance transformation weights (Average Rank Transformation Into Weight – ARTIW) method, the main normalized subjective weighting factors that most influence the conditions of transport of dangerous goods for safe transport have been identified. The results of the study revealed that the main factors of Group I that have the greatest impact on the accident of dangerous goods by railway, are: complete preparation of the train, driver’s confidence in the safety systems of the locomotive and improper loading of cargo. The most important technical-technological factors of Group II, which have the greatest impact on the accident occurring in the transportation of dangerous goods by railway, are: technical condition of the locomotive, tightness of railway tanks (wagons) and marking of wagons carrying dangerous goods. Key organizational factors for Group III to consider before dangerous goods are transported by railway are: risks related to freight forwarding, identification of chemical properties of freight and driver qualification. The key factors in these three groups can be used to develop models to make the transport of dangerous goods by railway safer and more efficient.